Some debatable problems of tick-borne encephalitis - N. I. Komandenko; N. G. Zhoukova (Бюллетень сибирской медицины, 2006)
The article presents the modernest sides of epidemiological of tick-borne encephalitis (TBE). In features were analysed clinical manifestitions and pathomorphosis of TBE in side soften symptomes of the infection. It presents debatable problems about seroneg- ative and chronic form of TBE and chronic containing virus—TBE in blood without manifestitions. It considers some questiones of pathogeny of differences form disease. The schemes were offered for rehabilitation patientes after TBE.